Potency of Culled Saanen Crossbred Goat in Supplying Raw Meat for Traditional Thai Butchery - A. A. Putra; S. Wattanachant; C. Wattanachant (Media Peternakan, 2017)
Potency of culled Saanen crossbred goat meat to replace the supply of yearling Boer crossbred goat meat was evaluated. Selected muscles from leg and shoulder cuts were analysed for their nutritional (proximate composition, collagen, amino acids, fatty acids), physicochemical (pH, myoglobin, drip loss, cook loss, shear force, lightness (L*) redness (a*) yellowness (b*), microstructure), and sensory (triangle test, hedonic test) evaluations. Meat samples from culled Saanen crossbred goat exhibited higher values in protein, collagen, and MUFA (P<0.05) than those from Boer crossbred goat, while lower values in ash, soluble collagen, and SFA were obtained (P<0.05). Meat from culled Saanen crossbred goat revealed higher cook loss, shear force, and redness compared to those from a yearling Boer crossbred goat (P<0.05). In addition, thicker perimysium in meat of Saanen crossbred goat was obtained particularly that could be seen on leg part. In sensory evaluation result, the panels could detect the differences between raw meat characteristics of these goat breeds (P<0.05) within the same muscle. However, the panels could not distinguish the difference between breeds in leg meat after being cooked. Shoulder meat of Saanen crossbred goat had less acceptance level compared to the other samples (P<0.05) particularly on its texture and taste quality. In summary, shoulder cut of culled Saanen crossbred goat exhibited a well-intentioned potency to substitute the supply of meat from yearling Boer crossbred goat. Nevertheless, pre-treatment might be applied to leg cut of Saanen crossbred goat to solve the less acceptance level of its textural and taste characteristics.